Communicative processes in the management of water resources: information and mobilization on the sub-basin committee of Salgado River, Ceara. - InÃs Prata GirÃo (2014)
This paper addresses the communicative relationships between those who make up the Committee of Sub-Basin Salgado, in the region of Cariri, Ceara, in light of both language and information sharing, considering the relationship between the members of the collegiate and the government as well as the status of representation within this group and the community. Open interviews and questionnaires were applied to 50% of the members of the Salgado Basin Comittee, who claim to have no problems with the understanding of scientific language, but consider that the information is retained and not shared. The segment represented by the government appears to be the less representative collegiate and demonstrates interest in having a more effective participation in the âlifeâ of the basin. Once the results were analyzed, recommendations were made to ensure the democratization of knowledge and information, respecting the different levels of education and widening the dialogue with the society. After analysing the results, it is concluded that the access to knowledge and information were mechanisms of empowerment, as well as support for the progress of the group. Nevertheless the college has not yet reached a level where sharing takes place completely through the dialogic communication that is described by the authors of the Communication and Education sciences. For this to happen, some recommendations were made, such as offering open courses to the counselors and to the community using new methods of communication that facilitate the understanding of technical content like graphical computer animation. It was also suggested the production of a radio magazine in order to disseminate, in popular language, scientific concepts in the area of water resources, what would ensure the debate and broaden the dialogue with society.